Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini) - Perreau, Michel (Zootaxa, 2019)
The discovery of the new species Halbherria daffneri Perreau, n. sp., a troglobitic species with pholeuonid body shape, in the high altitude karst system of Piani Eterni in southern Dolomites (northern Italy) is taken as an opportunity for a morphological investigation of the phylogeny of Bathysciotina with a special emphasis to the Italian genera. The monophyly of the set of Italian genera, (Aphaotus, Halbherria, Lessiniella, Neobathyscia, Sinuicollia) is confidently supported, with Neobathysica as the sister group of the four other genera. However the monophyly of the subtribe Bathysciotina is not significantly supported and the genus Sphaerobathyscia should clearly be excluded from the subtribe. The subgenus Albanella of the genus Speonesiotes is raised to genus rank.